Customization of a University Graduate: Illusion or Requirement of Time? - I. O. Leushin; I. V. Leushina (Moscow Polytechnic University, 2020)
The article focuses on the problems of the implementation of the educational process in the University, taking into account the interests and needs of employers in the context of the transition of Russian higher education to the updated educational standards designed to take into account the requirements of applicable professional standards. The reasons of emergence of a situation, when a young specialist, sharply focused on the needs of a particular employer is unable to solve professional problems in conditions of other industrial sites and laboratories. The authors demonstrate the negative effects of the so-called «in-depth professionalization» and isolation of graduates from the competition held by the University in the interests of the particular employer. The article dwells on the preventive measures to eliminate these phenomena in the framework of «university - employer » cooperation, taking into account the individual interests of the student who is originally a full stakeholder of educational process. The term «customization» derived from marketing means fine tuning of graduates according to the specific requirements of a particular employer. The article provides a critical analysis of customization with regard to the Russian higher education in the historical aspect. The authors substantiate the need of complex customization of graduates, which implies that all University partners and stakeholders should be involved in educational process. Such complex customization may engage regional resource centers, centers of competence, centers of excellence and centers of engineering which are free from corporate interests.